Safety and efficacy of cap-assisted EMR for sporadic nonampullary duodenal adenomas - Jamil, Laith H.; Kashani, Amir; Peter, Neiveen; Lo, Simon K. (Gastrointestinal endoscopy, 2017)
Eradication of sporadic nonampullary duodenal adenomas (SNADAs) is essential because of their high rate of malignant transformation. EMR techniques are the alternative to the traditional surgical treatments of SNADAs. There are very limited data on the safety and efficacy of cap-assisted EMR (C-EMR) in the treatment of SNADA. The medical records of patients who underwent C-EMR for SNADAs between July 2002 and April 2013 were retrospectively reviewed. Eradication was defined as no residual adenoma on follow-up or en bloc resection on pathology. Recurrence was defined as finding adenoma after a negative follow-up. Fifty-nine C-EMR sessions were performed on 49 SNADAs (flat, 46; sessile, 3); 39 polyps were treated in piecemeal fashion and 10 polyps with en bloc resection. The polyp histology was tubular adenoma (63.3%) and tubulovillous adenoma (36.7%), with 16.3% of lesions showing high-grade dysplasia. Initial eradication rate was 90.5%; residual adenomas were successfully treated with repeat C-EMR/snare, resulting in 100% ultimate eradication rate without any recurrences (median follow-up of 17 months). The overall adverse events rate was 16.9%: intraprocedural bleeding (10.2%), delayed GI bleeding (5.1%), and perforation (1.7%). Among large polyps (≥15 mm), the initial and ultimate eradication rates were 87.9% and 100%, respectively, and the adverse event rate was 17%. Initial eradication rate for small polyps was higher than in large polyps (100% vs 87.9%, respectively; P = .02). C-EMR is a highly efficient and safe method for the treatment of SNADAs. We recommend that endoscopists should learn C-EMR on esophageal, gastric, rectal, or left-sided colonic lesions before attempting C-EMR in the duodenum.